Agritourism in Africa - Nyagadza, Brighton; Chigora, Farai; Hassan, Azizul (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"This insightful, timely and multi-faceted book offers significant insight into the role and complex dynamics of agritourism in Africa. This volume will be of pivotal interest to students, researchers and scholars of Tourism, African Studies and Development Studies"--
Keywords: Agritourism -- Africa; BUSINESS & ECONOMICS / Industries / Hospitality, Travel & Tourism